2016
DOI: 10.1148/radiol.2015151120
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Tags on CT Scans to Predict Visceral Pleural Invasion of Non–Small Cell Lung Cancer That Does Not Abut the Pleura

Abstract: Type 2 pleural tags on conventional CT images can increase the accuracy of early diagnosis of visceral pleural invasion by NSCLC that does not abut the pleura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 16 publications
4
98
1
Order By: Relevance
“…Moreover, Ebara et al found that patients with VPI tended to be older than patients without (68.5 vs. 65.9 years; P=0.061) (8). However, other studies did not find any difference of age between patients with VPI and those without (9,10,15,16,20,21). But surprisingly, in our study, older age was found to be a significantly correlated factor of VPI in early-stage NSCLC (OR =2.119, 95% CI: 1.255-3.503; P=0.005) in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Moreover, Ebara et al found that patients with VPI tended to be older than patients without (68.5 vs. 65.9 years; P=0.061) (8). However, other studies did not find any difference of age between patients with VPI and those without (9,10,15,16,20,21). But surprisingly, in our study, older age was found to be a significantly correlated factor of VPI in early-stage NSCLC (OR =2.119, 95% CI: 1.255-3.503; P=0.005) in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies have also proved that pleural indentation was an independent predictive factor of VPI in lung cancer (9,10). Because pleural indentation may suggest the existence of a tumor infiltrating the pleural or pleural dissemination, it serves as a sign suggestive of pulmonary malignancy and possible diagnosis of VPI (9,10,21). Therefore, our study added to the evidence that pleural indentation was a significantly correlated factor of VPI in early-stage NSCLC.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…High-resolution CT imaging also offers the opportunity to better visualize changes in the alveolar spaces and interstitium, which conceivably may reveal underlying tumor biology or prognosis. The most apparent of these relationships is the association between pleural tags as seen on CT imaging with visceral pleural invasion by the tumor [23].…”
Section: Commentmentioning
confidence: 99%
“…Ebara et al [ 7 ] reported that a skirtlike 3-dimensional pleural pattern predicts pleural invasion of peripheral NSCLC with 77% accuracy. Our previous study [ 18 ] further reported that a pleural tag with a soft tissue component at the pleural end on a mediastinal window images predicts visceral pleural invasion of non-abutting NSCLC with 71% accuracy. [ 18 ] Whether visceral pleural invasion is an adverse prognostic indicator in stage I NSCLC patients remains controversial, especially in patients with a small tumor size.…”
Section: Discussionmentioning
confidence: 97%